Kajian Yuridis Kedudukan Pengemudi Ojek Online dalam Sistem Hukum Ketenagakerjaan di Indonesia - Julius Caesar Transon Simorangkir (VISA: Journal of Vision and Ideas, 2024)
The presence of online motorcycle taxis has had a significant impact in reducing unemployment in Indonesia. More than 4 (four) million people in Indonesia work as online motorcycle taxi drivers. This research uses a normative juridical approach and uses qualitative analysis techniques which are then explained and analyzed using descriptive analytical methods. This research aims to analyze the legal position of online motorcycle taxi drivers with online motorcycle taxi application service providers. The research results show that the legal position between online motorcycle taxi drivers and online motorcycle taxi application service providers is not part of the Employment Law system in Indonesia and is not subject to Law No. 13 of 2003 concerning Employment jo. Law number 6 of 2023 concerning the Stipulation of Government Regulations in Lieu of Law Number 2 of 2022 concerning Job Creation into Law. The author suggests that the Government make special regulations that regulate the legal position of Online Motorbike Taxi Drivers in the Employment Law System in Indonesia.